National variation in pulmonary metastasectomy for colorectal cancer - Fenton, HM; Finan, PJ; Milton, R; Shackcloth, M; Taylor, JC; Treasure, T; Morris, EJA (Wiley, 2021)
Aim Evidence on patterns of use of pulmonary metastasectomy in colorectal cancer patients is limited. This population‐based study aims to investigate the use of pulmonary metastasectomy in the colorectal cancer population across the English National Health Service (NHS) and quantify the extent of any variations in practice and outcome.